The Influence of Media Activity Book on Life Skills in Class VII Mental Retardation in SLB-B Negeri Pembina Palembang - Lestari, Annisa Ayu; Mawardah, Mutia (Universitas Muhammadiyah Metro, 2024)
This study aims to see the effect of activity books on life skills in seventh-grade mental retardation at SLB-B Negeri Pembina Palembang. This study used a quasi-experimental design with a one-group pretest-posttest design method. The subjects in this study were five seventh-grade mental retardation students at SLB-B Negeri Pembina Palembang who were still lacking in life skills. Researchers used pre-test and posttest questions, totaling 20 questions, which were assessed by homeroom teachers using a questionnaire and validated by researchers. The results showed an increase in the ability of students' life skills, which was marked by the rise in the average pre-test and posttest results. Based on the study's results, it can be concluded that activity book media affects the life skills of seventh-grade students. This can be used as an intervention to improve students' life skills that can be applied at school and home as a support for applying images to everyday life.